"... in order to Keep German Soil German": Austrian Burschenschaften, Nationalist Ethnopolitics and the South Tirol Conflict after 1945. (15th April 2014) - Weidinger, Bernhard
<x content-type="archive" xml:space="preserve">Abstract</x> Burschenschaften, as a particular type of German-nationalist (völkisch) student fraternity, have partaken in shaping Austrian politics in numerous ways since the nineteenth century. Acting as the standard-bearers of German nationalism in Austria after 1945 and being strongly represented in the ranks of the Freedomite Party of Austria (Freiheitliche Partei Österreichs/FPÖ), they have been able to maintain a degree of political relevance up until the present day—their intimate ideological, personal, and institutional entanglement with the National Socialist regime notwithstanding. Nonetheless, their history has so far almost exclusively been written by fraternity members themselves, and mostly in an affirmative, if not apologetic fashion; critical assessments for the post-1945 era in particular are limited to a small number of articles that, for the most part, are based on secondary literature rather than on primary sources.